ANTIDIABETES DAN PROFIL HISTOPATOLOGI SEL BETA PANKREAS PADA MENCIT MODEL INDUKSI STREPTOZOTOSIN EKSTRAK ETANOL DAUN RENGGAK (Amomum dealbatum L.) - Mislamah; Mislamah, Mislamah; Abdul, Abdul Rahman Wahid; Amalia, Ananda Ayu Amalia; Firma, Firma Amelia Kusuma; Safwan (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2025)
antidiabetic effects because their flavonoid levels are higher than the fruit. This study aims to determine the antidiabetic activity of ethanol extract of renggak leaves (EEDR), the optimal dose and the histopathological profile of the mouse pankreas. To determine its antidiabetic activity, a pre-test (initial blood sugar level before STZ induction) and post-test (after STZ induction) were carried out on the blood sugar levels of mice. A total of 36 male white mice were divided into 6 groups, namely normal group, negative group (Na-CMC 0.5%), positive group (Metformin 500 mg), EEDR group at doses of 240, 300, and 360 mg/kgBW.. Test results LSD posthoc showed that there was a mean difference between treatment groups with significant antidiabetic activity (p value <0.05). The ethanol extract group of renggak leaves was dosed at 240 mg/kgBW. The histopathological profile of the pankreas in each group showed extensive necrosis, the islets of Langerhans and inch tubules were difficult to distinguish, the cells looked degenerative with incomplete cytoplasm and degenerative nuclei.